Pengembangan Ekowisata Berbasis Masyarakat Pulau Pari Kepulauan Seribu Berdasarkan Analisis Faktor Lingkungan Internal dan Eksternal - Firdaus Hindra Hadi Saputro; Dhian Tyas Untari; Sugeng Suroso; Wastam Wahyu Hidayat (Jurnal Kajian Ilmiah, 2024)
The main challenge in sustainable tourism management is community involvement as one of the actors and at the same time beneficiaries of the development of the tourism sector. So that research on tourism hunting and placing the community with its wisdom as an inseparable part is important. The purpose of the study is to describe the strengths and weaknesses as well as opportunities and obstacles in developing community-based ecotourism on Pari Island, Seribu Islands, while specifically this study aims to secure existing tourism resources so that they can be utilized as much as possible to improve the economy and welfare of the community. The study uses a qualitative method. The study consists of three stages, namely the data collection stage, the data processing stage and the Conclusion Drawing Stage. This study does not only develop tourism at the destination but also places the community as actors and beneficiaries of the advantages of the tourism sector.